2007
DOI: 10.1080/10408440701524949
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the Design and Interpretation of Chronic Toxicity and Carcinogenicity Studies in Rodents: Approaches to Dose Selection

Abstract: For more than three decades chronic studies in rodents have been the benchmark for assessing the potential long-term toxicity, and particularly the carcinogenicity, of chemicals. With doses typically administered for about 2 years (18 months to lifetime), the rodent bioassay has been an integral component of testing protocols for food additives, pesticides, pharmaceuticals, industrial chemicals, and all manner of byproducts and environmental contaminants. Over time, the data from these studies have been used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 164 publications
0
32
0
4
Order By: Relevance
“…The cost, depending on route of administration, number of doses to be examined, and chemical being evaluated can range from $2-4 million, or even more for certain routes of administration, such as inhalation. The highest dose given is a maximum tolerated dose (MTD) and usually includes some evidence of toxicity, such as decreased weight gain (Rhomberg et al 2007). Extrapolation from the high doses used in these animal experiments to exposures in humans, particularly for nonpharmaceutical chemicals for which there frequently are several orders of magnitude difference in exposure between rodents in the bioassays and humans, has been the source of considerable controversy (Ames and Gold 1990;Rhomberg et al 2007;Flamm and Winbush 1984;Slikker et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost, depending on route of administration, number of doses to be examined, and chemical being evaluated can range from $2-4 million, or even more for certain routes of administration, such as inhalation. The highest dose given is a maximum tolerated dose (MTD) and usually includes some evidence of toxicity, such as decreased weight gain (Rhomberg et al 2007). Extrapolation from the high doses used in these animal experiments to exposures in humans, particularly for nonpharmaceutical chemicals for which there frequently are several orders of magnitude difference in exposure between rodents in the bioassays and humans, has been the source of considerable controversy (Ames and Gold 1990;Rhomberg et al 2007;Flamm and Winbush 1984;Slikker et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The highest dose given is a maximum tolerated dose (MTD) and usually includes some evidence of toxicity, such as decreased weight gain (Rhomberg et al 2007). Extrapolation from the high doses used in these animal experiments to exposures in humans, particularly for nonpharmaceutical chemicals for which there frequently are several orders of magnitude difference in exposure between rodents in the bioassays and humans, has been the source of considerable controversy (Ames and Gold 1990;Rhomberg et al 2007;Flamm and Winbush 1984;Slikker et al 2004). Most importantly, during the past several years, several examples have been identified that raise the question of the relevance of the tumors induced in the rodent bioassay to assessing human risk (Cohen 2004; International Agency for Research on Cancer [IARC] 1999a; Meek et al 2003;Cohen et al 2004;Seed et al 2005;Boobis et al 2006Boobis et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The standard design of the 2-year bioassay includes a rigorous sampling of all masses and a tissue types (Sontag et al, 1976). It is also intended to test the maximum tolerated dose (MTD) of the test article (Rhomberg et al, 2007). However, these design elements favor detecting potent genotoxic carcinogens, agents with relatively high MTDs and detecting macroscopic lesions and tumors that decrease life-span (Gaylor, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…But NTP started adding a third lower test article-treated dose group to nullify the effects of overt toxicity and excess mortality in the high-dose groups and to provide a safety margin against overestimation of MTD. The third-dose group was also added because having only 2 test article-treated dose groups did not provide information on dose response relationship or trends and no observed effect level (NOEL) or no observed adverse effect level (NOAEL; Sontag, Page, and Saffiotti 1976;Haseman 1984Haseman , 1985Hayes et al 2011;Hess, Bretz, and Gfeller 1983;Portier and Hoel 1984;Rhomberg et al 2007). Since our findings clearly demonstrate that the high-dose group at MTD could not detect a carcinogenic effect while the mid and low doses served the purpose in detecting the true carcinogenic potential of the assay, a high dose set at MTD is not needed.…”
Section: Discussionmentioning
confidence: 99%